Learning disabilities teachers’ perceptions of employing artificial intelligence applications in teaching their students - Alnaim, Mariam; Al-Otaibi, Ghada (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study explores the learning disabilities teachers’ perceptions of employing artificial intelligence (AI) applications in teaching their students in Saudi Arabia. A quantitative approach was utilized, distributing a questionnaire to 108 teachers of students with learning disabilities. Findings indicate a moderate level of AI application use, with tools like virtual reality (VR) and speech recognition being more commonly recognized and valued. However, other applications, such as Thinkster Math, remain underutilized, revealing gaps in effective AI integration. The study recommends targeted strategies to overcome barriers such as insufficient teacher training, lack of digital infrastructure, and the need for culturally responsive AI tools. Key solutions include developing professional development programs, improving access to technology, and providing financial incentives to encourage wider adoption. By addressing these challenges and implementing these recommendations, Saudi Arabia can enhance its special education landscape, enabling teachers to leverage AI as a transformative tool and fostering a more inclusive and adaptive learning environment for students with learning disabilities. This study underscores the need for continuous research and feedback to refine AI tools, ensuring they meet educational goals and improve student outcomes.